Principles of Chemical Engineering Practice - DeLancey, George (Wiley, 2013)
Integrating scientific principles with practical engineering experience, this text enables readers to master the fundamentals of chemical processing and apply their knowledge of such topics as material and energy balances, transport phenomena, reactor design, and separations across a broad range of chemical industries. The author skillfully guides readers step by step through the execution of both chemical process analysis and equipment design.